2022
DOI: 10.1001/jamanetworkopen.2022.21430
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Prospectively Comparing Opioid Analgesia With Opioid-Free Analgesia After Outpatient General Surgery

Abstract: IMPORTANCEThe overprescription of opioids to surgical patients is recognized as an important factor contributing to the opioid crisis. However, the value of prescribing opioid analgesia (OA) vs opioid-free analgesia (OFA) after postoperative discharge remains uncertain. OBJECTIVE To investigate the feasibility of conducting a full-scale randomized clinical trial (RCT) to assess the comparative effectiveness of OA vs OFA after outpatient general surgery. DESIGN, SETTING, AND PARTICIPANTSThis parallel, 2-group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…Of course, the novelty of the study by Do et al is not in the desire to identify an optimal strategy for managing postoperative pain but in specifically establishing the feasibility of studying the impact of opioid-free pain management. This extends at least in part from literature that showed that rates of new persistent opioid use, defined as previously opioid-naive patients filling opioid prescriptions more than 90 days after their index procedure, were 5.9% and 6.5% after minor and major surgery, respectively .…”
supporting
confidence: 57%
See 4 more Smart Citations
“…Of course, the novelty of the study by Do et al is not in the desire to identify an optimal strategy for managing postoperative pain but in specifically establishing the feasibility of studying the impact of opioid-free pain management. This extends at least in part from literature that showed that rates of new persistent opioid use, defined as previously opioid-naive patients filling opioid prescriptions more than 90 days after their index procedure, were 5.9% and 6.5% after minor and major surgery, respectively .…”
supporting
confidence: 57%
“…As the medical community continues to highlight the many causes and consequences of the present opioid crisis in North America, opioid-free perioperative analgesia has emerged as one potential strategy to mitigate a key factor associated with chronic opioid use. It was with interest, then, that I reviewed the article by Do and colleagues, written on behalf of the McGill Better Opioid Prescribing Collaboration. The authors detailed the results of an assessor-blinded, pragmatic pilot randomized clinical trial investigating the feasibility of conducting a full comparative effectiveness trial of prescribing postoperative opioid analgesia compared with opioid-free analgesia among patients undergoing outpatient general surgery.…”
mentioning
confidence: 99%
See 3 more Smart Citations